Can Kuznets curve hypothesis explain the mission drift of microfinance institutions? Evidence from developing countries - Md Aslam Mia; Adamu Jibir; Arpita Sharma; Musa Abdu (Asia and the Global Economy, 2023)
In order for microfinance institutions (MFIs) to significantly impact the society, they must achieve both financial sustainability and outreach goals simultaneously. However, when MFIs prioritize financial sustainability at the expense of their outreach goals, it is regarded as mission drift. This study introduces the concept of the Kuznets curve hypothesis to explain the occurrence of mission drift in MFIs. By analysing data from 1,323 unique MFIs across 105 emerging countries, between 2010 and 2018, our findings corroborate the existence of the Kuznets curve for outreach and financial goals. The findings demonstrate that MFIs initially prioritize their outreach goal of serving more female clients but gradually shift focus towards financial performance as they expand and accumulate fixed assets. Moreover, we also empirically quantified the critical asset size of MFIs beyond which they are less likely to achieve their outreach and financial sustainability goals. The implications of these findings for policy are also discussed.